ANALYSIS OF POVERTY, UNEMPLOYMENT AND COMMUNITY CONFLICT ON CRIME IN BINJAI CITY - Yuanda Afandi; Jariah Abubakar; Asnawi; Ichsan (PT. Radja Intercontinental Publishing, 2024)
The study was conducted to analyze the extent to which social conditions such as poverty, unemployment, and local conflicts affect the occurrence of crime. The study was conducted in Binjai city, North Sumatra. This study uses secondary data in time series form covering a period of 22 years from 2001 to 2022. EViews 10 multiple regression analysis was used for the data processing model. The results show that poverty variable has a partial negative insignificant effect on crime, unemployment variable has a positive insignificant effect and community conflict variable has a positive significant effect on crime.Community conflict variable is the major factor affecting crime in Binjai city. Meanwhile, variables such as poverty, unemployment and conflicts in society have a positive and significant impact on the crime rate in Binjai city.